Identity and Place from 1971 to 2009: Constructions of Land and Geography in Saskatchewan’s Social Studies Education - Porter, Gemma (Journal of the Canadian Association for Curriculum Studies, 2025)
This article examines discourses of land and place in Saskatchewan Grade 9 to 12 social studies and history curriculum from 1971 to 2009. As such, the study provides insight into the function of discourses about land and place and situates these discourses in the broader context of enduring and dominant myths at the intersections of place and identity in Canada. As modern urban living undermines our connections to the landscapes we inhabit, this study provides a timely examination of both the notion of place in Canadian identity, as well as its current conception in social studies curricula in Saskatchewan.